AN INSIGHT INTO VERRUCOUS CARCINOMA (World Journal of Current Medical and Pharmaceutical Research, 2019)
Verrucous carcinoma (VC) is a variant of squamous cell carcinoma often referred to as snuff dippers cancer because of its high rate of incidence in those who use snuff. A patient aged 57 years reported with a chief complaint of white growth in the left cheek region since 1 year. The growth was gradual in onset, and increased size since the patient noticed it. No history of pain, bleeding, or difficulty in swallowing was reported. No history of any topical application and no similar growths were noticed elsewhere in the body. The left cervical lymph nodes were involved to level 3 which were around 1 cm diameters soft and movable. Intraorally, a well-defined keratotic mass with finger-like projections on the surface was present of 5 cm × 4cm, roughly oval in shape, well-defined borders on buccal mucosa at the level of occlusal plane near the molar region extending anteriorly till the commisure of the lip. Based on the clinical appearance provisional diagnosis of VC was given after which incisional biopsy taken confirmed the lesion as verrucous hyperplasia (VH).Verrucous carcinoma is best treated with surgical excision of the lesion, which was already proven and has less chances of recurrence.